Inter-ocular facilitation and suppression in the reading of Chinese characters - Li, Ling-Ya (The University of Edinburgh, 2011)
An overwhelming amount of research has generalized rules to the psycholinguistic mechanisms underlying visual word recognition. Most theories are based on studies of Indo-European languages in general, English in particular. Naturally, due to the universal principal of language, some researchers believe that the application of theories of language processing is universal despite that they were built on observations from specific languages. Conversely, other researchers think that language-specific variations warrant different psycholinguistic mechanisms for typologically different languages. To resolve the tension between the two perspectives, cross-linguistic methods in language processing thus become the focus of the field. Comparisons across languages allow researchers to investigate the universalities and the specificities of language processing. Therefore, in recent years, researchers have shown an increased interest in the study of non-alphabetic languages because of its different formats in the way that various orthographies represent spoken languages. Much debate has focused on whether orthographic-specific processing is related to the reading of different orthographies.
Keywords: Inter-ocular Facilitation; Suppression